Depression-like Behavior Induced by Nesfatin-1 in Rats: Involvement of Increased Immune Activation and Imbalance of Synaptic Vesicle Proteins - Ge, Jin-Fang; Xu, Ya-Yun; Qin, Gan; Peng, Yao-Nan; Zhang, Chao-Feng; Liu, Xing-Rui; Liang, Li-Chuan; Wang, Zhong-Zheng; Chen, Fei-Hu (Frontiers in Neuroscience, 2015)
Depression is a multicausal disorder and has been associated with metabolism regulation and immuno-inflammatory reaction. The anorectic molecule nesfatin-1 has recently been characterized as a potential mood regulator, but its precise effect on depression and the possible mechanisms remain unknown, especially when given peripherally. In the present study, nesfatin-1 was intraperitoneally injected to the rats and the depression-like behavior and activity of the hypothalamic-pituitary-adrenal (HPA) axis were evaluated. The plasma concentrations of nesfatin-1, interleukin 6 (IL-6), and C-reactive protein (CRP); and the hypothalamic expression levels of nesfatin-1, synapsinⅠ, and synaptotagminⅠmRNA were evaluated in nesfatin-1 chronically treated rats. The results showed that both acute and chronic administration of nesfatin-1 increased immobility in the forced swimming test (FST), and resulted in the hyperactivity of HPA axis, as indicated by the increase of plasma corticosterone concentration and hypothalamic expression of corticotropin-releasing hormone (CRH) mRNA. Moreover, after chronic nesfatin-1 administration, the rats exhibited decreased activity and exploratory behavior in the open field test (OFT) and increased mRNA expression of synapsinⅠand synaptotagminⅠin the hypothalamus. Furthermore, chronic administration of nesfatin-1 elevated plasma concentrations of IL-6 and CRP, which were positively correlated with despair behavior, plasma corticosterone level, and the hypothalamic mRNA expression of synapsinⅠ and synaptotagminⅠ. These results indicated that exogenous nesfatin-1 could induce the immune-inflammatory activation，which might be a central hug linking the depression-like behavior and the imbalanced mRNA expression of synaptic vesicle proteins in the hypothalamus.